Cost estimation of an asteroid mining mission using partial least squares structural equation modelling (PLS-SEM). (February 2020) - Probst, A.; Nitzl, C.; Kraus, F.; Förstner, R.
Abstract: One of the biggest challenges of a mining endeavour lies in the judgement of its economic feasibility such as the estimation of costs and the prediction of the market value of the designated product. Whereas the complexity of the latter originates mainly from the supply and demand of the economic situation, the complexity of the first derives from the lack of heritage data, the high degree of innovation and the uncertainties that are connected to any long-term project. In this paper, the authors apply a cause-effect analysis technique called structural equation modelling (SEM) using partial least squares (PLS) to estimate the costs of an asteroid mining mission concept called KaNaRiA. For data ascertainment, two expert interview rounds have been conducted involving international space engineers and scientists from different professional levels and areas. First, a qualitative method called the Delphi technique is used to identify the main cost drivers and quantify their influence on the overall costs. Second, the cost drivers were formulated as questions to enable the classification on a Likert-scale. The collected data is the input for the development of the cost prognosis model by applying PLS-SEM. The cost model is given and its usage explained. The resulting cost model allows a user-individual estimation of the mission costs depending on the individual judgement of the influence of the final, relevant cost drivers. An application of the model using the judgment of the authors' is presented. Highlights: The paper successfully demonstrates an approach for cost assessment of space missions with no heritage data. The main cost drivers of an asteroid mining mission were identified. The importance and their effect on the overall mission costs have been estimated. A final cost model for the estimation of an asteroid mining mission has been established.